ANOTACIONES SOBRE LOS LAGOMORPHA Y RODENTIA DEL PARQUE NACIONAL NATURAL CHINGAZA (111) - Pérez Torres, Jairo; Laboratorio de Ecología de Poblaciones. Departamento de Biología, Departamento de Biología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2013)
This paper compilates information obtained from field and Jaboratory work, bibliography research and interviews in the field, for Lagomorphs and Rodents in Chingaza National Pilrk. The information compilated includes common name, taxonomic description, natural history and geographic distribution of each species.